Development of a model for the estimation of financial processes in logistic systems at industrial enterprises - Bondarenko, Olena; Palyvoda, Olena; Kyrylenko, Oksana (Eastern-European Journal of Enterprise Technologies, 2018)
The model and the method for assessment of the effectiveness of management of financial processes in logistic systems of industrial enterprises were substantiated. The model takes into consideration the parameters of financial flows and their cumulative effect on overall efficiency. The method was developed based on calculation of the integral index by the criteria of liquidity, balance, intensity, and sufficiency of financial flows, taking into consideration the structure of factor features. The groups of factors were generated based of the methods for data standardization and actualization, which determine the key criteria for the management of financial processes at industrial enterprises under conditions of logistication of economy. The economic content of correlation dependences between the latent factors and their variables was interpreted. The level of influence of the key criteria on the general state of management of financial processes in logistic systems was determined with the use of the methods of taxonomy. The formula of calculation of the integral index was proposed in order to ensure a reliable assessment of the final state of the management of financial processes (high, medium, low, rather low). The permissible limits of its fluctuations were established by the method of the Shewhart control charts. The application of the model provides the design of objective recommendations regarding decision-making on the regulation of the corresponding indicators in the context of the selected key criteria. The software IBM SPSS Statistics (Russia) was used for the calculations, which makes it possible to analyze the values of arrays of information and level the errors in justifying decisions. The proposed model can be useful for economic entities in the international format. It opens up additional possibilities for evaluation, taking into consideration the life cycle of an enterprise, industrial tendencies, the stage of logistication of the world economy.